Pyrolytic Carbon Electrodes and Their Potential Application in Electrochemical Sensors - Nguyen, Thi Thanh Ngan; Bui, Thanh Giang; Nguyen, Danh Thanh; Nguyen, Duc Thanh; Nguyen, Hoang Long; Nguyen, Tuan Hong; Dang, Thanh Binh; Vu, Thi Thu (Communications in Physics, 2022)
In this work, pyrolytic carbon electrodes were prepared through pyrolysis of well-patterned AZ 1505 positive photoresist films. The designed electrodes firstly were prepared via photolithography technique, then the polymer was thermally broken-down into carbon skeletons in an oxygen-free environment using pyrolysis technique. The effect of the highest temperature and ramping rate on the electrical properties of the carbon films were investigated. The results show that the pyrolysis process was optimal at the ramping rate of 3 °C/minute, annealing temperature of 900 °C, and annealing time of one hour. The lowest resistivity was obtained at 6.3 ´ 10-5 Wm for pyrolytic films prepared at the optimal pyrolysis conditions. Electrochemical measurements confirm the potential of this electrode for electrochemical sensing applications.